Formation and activation of defects in films of AIVBVI compounds in the process of growing from vapor phase - Saliy, Ya.P.; Freik, I.M.; Prokopiv (Jr), V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The work has suggested an adequate model describing formation of defects in
films of AIVBVI compounds in vapor-phase growth. Being based on this model, it has
given an analytical description of dependences for film electrophysical parameters
(concentrations n, p and mobilities µn, µp of free charge carriers) on technological factors
of film growth. We have calculated concentrations of activated and inactivated defects as
subject to temperature of film deposition. The developed model enables determination of
entropy and enthalpy of defect formation processes.